An Active Balancing Method Based on SOC and Capacitance for Lithium-Ion Batteries in Electric Vehicles - Liu, Renxiong; Zhang, Chaolong (Frontiers in Energy Research, 2021)
An active balancing method based on state of charge (SOC) and capacitance is presented in this paper to solve the inconsistency problem of lithium-ion batteries in the battery packs of new energy vehicles. The terminal voltage of each battery is collected firstly. Then, each battery SOC is estimated by an extended Kalman filter (EKF) algorithm accurately. In the experiment, the battery SOC evaluation maximum absolute error is 0.0061 and the mean absolute error is 0.0013. Afterward, an active balancing circuit based on the estimated battery SOC and capacitance is designed. The energy of capacitor is charging by the battery whose SOC is higher than the other batteries through the circuit in order to avoid the battery being overcharged. Then, the SOC of batteries gradually turn consistency. In the simulation experiment, the SOC difference of batteries is 7% before the batteries are charged. Meanwhile, the SOC difference of batteries reduces to 0.02% after the balancing and the consuming time is merely 272s, which manifests a fast balancing speed and balancing efficiency.